Formation and thermal stability of NiSi phase in Ni (30 nm)/Pt (2 nm; 6 nm)/Siep. (50 nm)/Si (001) thin film systems - Makogon, Iu.N.; Pavlova, E.P.; Sidorenko, S.I.; Beddies, G.; Beke, D.L.; Csik, A.; Verbitska, T.I.; Fihurna, E.V.; Shkarban, R.A. (Functional Materials, 2013)
The influence of Pt on solid state reactions in Ni (30 nm)/Pt(x) /Siep.(50 nm)/ Si (001) (x=2 nm, 6 nm) nanodimensional films has been investigated. The layers of Pt and Ni were produced by magnetron sputtering technique on the epitaxially grown 50 nm Si layer on the top of the monocrystalline Si (001) substrate at the room temperature. Isochronal rapid thermal annealing of the samples was carried out in nitrogen atmosphere for 30 s in (450—900)° C temperature range. In the as-deposited films no phase formations were observed. During heat treatments thermally activated solid state reactions began by formation of intermediate silicide phase of Ni₂Si for x=2 nm, but the formation of this Ni reach phase was hindered for x=6 nm. Increasing the annealing temperature up to 600° C, independently from the thickness of the intermediate Pt layer, NiSi , PtSi compounds as well as Ni₁₋xPtxSi solid solution have been formed. Two-layered heterostructure has been observed for x=6 nm: complex polycrystalline Ni₁₋xPtxSi phase formed close to the surface, below which the NiSi phase was situated. Decomposition of Ni₁₋xPtxSi silicide to the NiSi (and PtSi ) phases was observed after annealing above 650° C and 850° C. Si enrichment at the surface of the Ni₁₋xPtxSi , NiSi and NiSi₂ phases is clearly observed on secondary neutral mass spectrometry depth profiles, which is interpreted as a consequence of the fast diffusion of Si along the grain boundaries.